2017
DOI: 10.11646/zootaxa.4277.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Luciobarbus chelifensis and L. mascarensis, two new species from Algeria (Teleostei: Cyprinidae)

Abstract: Cyprinids of the genus Luciobarbus are the most abundant and widespread fishes in most freshwater ecosystems in the Maghreb. In the Mediterranean basin of Morocco, Algeria and Tunisia, all species of Luciobarbus—with exception of L. guercifensis—are superficially very similar and are distinguished mostly by minor morphometric characters. Molecular characters distinguish all species well and nine species are recognised from the area, two of them described here. Luciobarbus chelifensis, from the Chelif River dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 840 publications
(8 citation statements)
references
References 21 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…This study follows Casal-Lopez et al (2015), Doadrio et al (2016aDoadrio et al ( , 2016b and Brahimi et al (2017) in describing new species of African Luciobarbus based largely on molecular distances. We further made considerable efforts to detect external morphological characters usable for an univocal identification of the different Luciobarbus species from the African Mediterranean Sea basin.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This study follows Casal-Lopez et al (2015), Doadrio et al (2016aDoadrio et al ( , 2016b and Brahimi et al (2017) in describing new species of African Luciobarbus based largely on molecular distances. We further made considerable efforts to detect external morphological characters usable for an univocal identification of the different Luciobarbus species from the African Mediterranean Sea basin.…”
Section: Discussionmentioning
confidence: 79%
“…Doadrio et al (2016a) stated that L. moulouyensis from the Moulouya River drainage is a synonym of Carasobarbus fritschii and described the Luciobarbus previoulsly known as L. moulouyensis as L. yahyaouii. Finally, Brahimi et al (2017) presented an identification key of all Luciobarbus species found in the African Mediterranean Sea basin, a new set of molecular data and described two additional new species from Algeria (L. chelifensis & L. mascarensis).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on Mediterranean cypriniforms suggest that the species diversity and endemicity of these fishes is higher than previously estimated [6,7,12,16]. Considering the high host specificity of Dactylogyrus spp., the discovery of new species parasitizing Mediterranean cypriniforms can likewise be expected.…”
Section: Discussionmentioning
confidence: 84%
“…Doadrio et al (2016) described the species previously known as L. nasus in the Moulouya river watershed, as L. guercifensis. Finally, Brahimi et al (2017) presented an identification key for all Luciobarbus species found in the African watershed that flows into the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%